The Determinants of Physical Fitness Levels Among Young Adults Using the Harvard Step Test - hasanah, Nunung - (LPPM UNIKAL, 2025)
Background: Physical fitness is an important indicator of cardiorespiratory health in young adults. Various factors are thought to influence fitness, including age, sedentary behaviors such as mobile phone use, and body mass index (BMI). However, empirical evidence regarding the relationship between these factors and physical fitness still shows mixed results. Objective: This study aims to analyze the relationship between age, duration of mobile phone use, and BMI on physical fitness levels as measured using the Harvard Step Test. Methods: This study used an observational analytical design with a cross-sectional approach. A total of 16 young adult respondents participated in the study. Data collected included age, duration of daily mobile phone use, BMI, and fitness scores based on the Harvard Step Test. Data analysis was performed using the Spearman correlation test with a significance level of 0.05. Results: The analysis showed no significant relationship between age and fitness (p = 0.073; r = -0.460), duration of cell phone use and fitness (p = 0.353; r = -0.249), and BMI and fitness (p = 0.562; r = -0.157). However, all variables showed a negative correlation with fitness levels. Conclusion: Age, duration of cell phone use, and BMI did not show a significant relationship with physical fitness levels in young adults based on the Harvard Step Test. This finding indicates that other factors, such as physical activity level and exercise habits, may play a greater role in determining physical fitness. Keywords: physical fitness, Harvard Step Test, body mass index, cell phone use